Integrasi Hadist dalam Kebijakan Ekonomi Syariah dalam Perspektif dan Tantangan - Hidayatullah Hidayatullah; Fadllan Fadllan (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research discusses the integration of hadith in sharia economic policy, with a focus on perspectives and challenges. The main objective of this research is to analyze the role of hadith as a legal source in formulating economic policies based on sharia principles, as well as to identify the challenges faced in its implementation. The method used in this research is qualitative with a literature study approach, which examines various written sources, such as books, articles and scientific journals related to the topic of sharia economics and hadith. The research results show that the hadith provides important guidelines in regulating various aspects of the economy, including the prohibition of usury, the principle of fairness in transactions, and the importance of zakat and waqf. However, major challenges in integrating hadith into sharia economic policy include differences in interpretation of hadith, incompatibility with the modern economic system, and a lack of in-depth understanding of sharia economics among policy makers. This research concludes that although these challenges are significant, the integration of hadith in sharia economic policy still has great potential to create a fairer and more sustainable economic system, as long as there is collaboration between ulama, academics and policy makers to overcome these obstacles.